2021
DOI: 10.1016/j.polymdegradstab.2020.109267
|View full text |Cite
|
Sign up to set email alerts
|

Thermal oxidation of poly(dicyclopentadiene) - Effect of phenolic and hindered amine stabilizers

Abstract: The thermal oxidation of stabilized polydicyclopentadiene was deeply studied here for the first time. Three kinds of antioxidants (phenolic antioxidant BHT, monomeric hindered amine in alkoxylated form Tinuvin 123 and oligomeric hindered amine Chimassorb 2020) were compared at the same concentrations. Tinuvin 123 was observed to me more efficient than Chimassorb 2020 because of the "activated" nature of alkoxyamine in Tinuvin 123. Results were simulated using a completed version of previously established kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…It could be the same in particular for the reaction between POO °and radical by products generated by stabilizer. This is in line with the first estimations of corresponding rate constants [56] where the rate constant for POO °+ phenoxy radical is about 5 L.mol −1 .s −1 at 50 °C vs 10 8 in model liquids.…”
Section: Runsupporting
confidence: 91%
“…It could be the same in particular for the reaction between POO °and radical by products generated by stabilizer. This is in line with the first estimations of corresponding rate constants [56] where the rate constant for POO °+ phenoxy radical is about 5 L.mol −1 .s −1 at 50 °C vs 10 8 in model liquids.…”
Section: Runsupporting
confidence: 91%
“…1.044 mmol in phenol function per 100 g of DCPD . Indeed, previous studies have shown that the use of more stabilizing agent in PDCPD does not improve its efficiency [20] . For comparison, incorporation of antioxidant in the PDCPD formulation has then been performed by bulk polymerization of DCPD in the presence of the commercially available stabilizing agent: hindered phenol BHT ( Scheme 3 ).…”
Section: Preparation Of Stabilized Pdcpd Filmsmentioning
confidence: 99%
“…Despite the presence of BHT, PDCPD undergoes oxidation that favors crosslinking leading to a large increase in glass transition temperature ( T g ) together with an increase in rubbery modulus and maximal stress [19] and, as a consequence, an embrittlement of the polymer. Use of the hindered amine light stabilizer (HALS) stabilizer Tinuvin 123 or Chimassorb 2020 instead of BHT allows to improve the protection performance especially when lowering the ageing temperature [20] .…”
Section: Introductionmentioning
confidence: 99%
“…More elaborated kinetic models are based on kinetic constants related to the specific degradation mechanisms [13,30]. As such models include rate constants of the processes involved in degradation, they are very accurate in lifetime prediction.…”
Section: Introductionmentioning
confidence: 99%